(3TQM fgL GdHdGZIs - (3CHhMGeO YRGdOjf YHO GdMejO Hf gHg Gddg Hf eMeO Hf GdMSjf Hf CHi GdMOjOs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3eMeO Hf Ydi Hf YeQGf Hf ajGV GdfYei GdHMQGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYGOd hef cdGe dg Ydjg GdSdGe ai eYfi WdMI (B: (3hbO cfJ heG CgOO HGdMQH s
(3BNQgG (B:s
(3hdgPG GdeYfi Sei CHhSajGf Hf MQH EHf YfHSI, hSei SYjO Hf GdYGU EHf YfHg hGdMeO ddg hMOg s
(3fSNI KGdKIs
(3cJHgG CcKQ ef fGSNs
(3hhHOGNdgG Jedc SfI (B1088(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs